Translation Study: Photograph App on a Jawi Arabic Text - Allif Syahputra Bania; Najihatul Faridy; Nuraini; Bachtiar Akob (proceedings.icesy, 2026)
Arabic Javanese (Jawi Arabic) is a cultural phenomenon that developed originally from the Veranda of Mecca region. The Javanese Arabic script has a strategic function which acts as a written language related to the dissemination of knowledge in various fields and religious studies. The Javanese Arabic script has been marginalized and experienced a phase of decline in responding to the challenges of the times and despite the fading and nearing extinction of the Jawi arabic script. It is necessary to understand and be able to use text recording applications for translation, which is a Google Lens feature that can be easily accessed via smartphones with internet access, where the translation results are obtained in real time. This research uses a qualitative descriptive. Data was obtained by using the text translation application on the Google Lens feature with the source language being Malay (Jawi) to the target language Indonesian. The Jawi Arabic script will be tested repeatedly using trial and error methods related to the quality of the translation. The result requires a quality upgrade.